Pengaruh corporate social responsibility pada kinerja keuangan perusahaan pertambangan - Putri Asiza Agustien Aulia Rahmah; Rr. Iramani (STIE Perbanas Surabaya, 2015)
The business people and their behavior need to understand their companies’ demand in the environment. They should also think about the whole stakeholders for manag-ing their business. Businessmen need to understand when a company operating there is a responsibility for stakeholder. In this research stakeholder are employees, suppliers, government, and environmental. The purpose of this research was to ex-amine the effects of Corporate Social Responsibility (CSR) toward the financial per-formance of a mining company in term of Return on Assets and Asset Turn Over. The analysis technique is using Multiple Regression Analysis (MRA). The result of this research shows that Corporate Social Responsibility affects Return on Asset and Asset Turn Over on a mining company. For that reason, business people should also pay attention to this factor in their business.